Waste Management and Circular Economy in the French Building and Construction Sector - Diemer, Arnaud; Nedelciu, Claudiu Eduard; Morales, Manuel E.; Batisse, Cécile; Cantuarias-Villessuzanne, Carmen (Frontiers in Sustainability, 2022)
The impact that European and French legislation have on the circular economy implementation between market-driven incentives and state regulation emerges as the main challenge addressed in this chapter. Circular economy principles and the normative aspects of legislation constitute the best available frameworks to foresee how circular economy implementation will evolve in the building and construction sector in France. The Eiffage case study can be explained by the evolution of the normative arena composed by the current codes, environmental laws, roadmaps and directives that frame the dynamic behavior of individual actors submitted to market pressures. A literature review of the current scientific and grey literature on circular economy in the building and construction sector was carried out in order to identify the required conditions to improve circularity in a normative way in France. Seven circular economy principles have been identified in the state of the art of Building and construction sector in France with emphasis on four of them: 1) Building lighter structures, 2) Waste reduction in the production process, 3) Intensive use of floor space and 4) Extension of product life or recycling. Finally, we claim that the advantage of the normative approach implementation and analysis is to set the social agreement of compulsory foundation over which the market-driven initiatives and innovation could make the difference for the outstanding stakeholders of the economic sector.